Evaluation of Undrained Bearing Capacities of Wide-Shallow Bucket Foundation with Honeycomb Bulkheads in Clay. (6th December 2019) - Wang, Qingshan; Han, Xun; Guan, Yunfei; Cao, Yongyong; Li, Wenxuan
Abstract : As a new type of offshore wind foundation, the wide-shallow bucket foundation with honeycomb bulkheads mainly bears vertical, horizontal, and moment loads. As yet, no systematic study has been conducted regarding the effects of honeycomb bulkheads on the undrained bearing capacities of the wide-shallow bucket foundation. In this study, a large number of three-dimensional (3D) finite element (FE) analyses were performed to investigate the undrained bearing capacities of the wide-shallow bucket foundations with and without honeycomb bulkheads, thereby evaluating the influence of honeycomb bulkheads on the bearing capacities under different conditions. The results show that under uniaxial loading, the uniaxial bearing capacities of the wide-shallow bucket foundation are basically unaffected by the honeycomb bulkheads in homogeneous clay. For nonhomogeneous clay, the moment bearing capacity will be considerably enhanced with the increase in soil shear strength heterogeneity. Under combined loading, the honeycomb bulkheads will enhance the combined bearing capacities only in nonhomogeneous clay. The enhancement effects will increase with the increase in soil shear strength heterogeneity but decrease with the increase in vertical load. Besides, the simplified equations for calculating the uniaxial bearing capacities of the wide-shallow bucket foundation with honeycomb bulkheads are also proposed considering the influence of embedment ratio and soil shear strength heterogeneity. At last, the parameters of an approximating expression are fitted to predict the failure envelopes of this foundation under combined loading.